Integrating Sustainability and Digital Advancements In Maritime Law Education: Enhancing Cadet Preparedness - Tri Cahyadi; Ahmad Ahmad; larsen Barasa (International Journal of Law and Society, 2024)
This research investigates the integration of sustainability principles and digital advancements in maritime law education within vocational training programmes. Drawing on qualitative perspectives from maritime professionals and educators, the study identifies critical areas for curriculum enhancement and skill development. Key findings highlight the industry's emphasis on regulatory compliance, safety management, and the use of digital technologies in maritime operations. The research underscores the importance of practical training modules, simulation-based learning, and industry partnerships in preparing cadets for real-world challenges. Expertise from industry stakeholders informs curriculum design, focusing on digital navigation tools, safety protocols, and regulatory frameworks like STCW and IMO standards. Assessment of cadet readiness reveals strengths in theoretical knowledge but emphasizes the need for more extensive practical training. Innovative approaches using simulators and online platforms enhance learning outcomes and operational efficiencies. The study concludes with recommendations for ongoing collaboration between academia and industry to sustain curriculum innovation and prepare a competent workforce for the evolving maritime industry.